Better to Be Loved By Some? Firm Flaunting as an Impression Management Strategy - Bass, A. Erin; Pfarrer, Michael D.; Milosevic, Ivana; Titus, Varkey K. (Academy of Management Review, 2023)
Firms can use a range of proactive impression management behaviors to reduce the impact of a negative event on firm outcomes. When a negative event is unpredictable, we theorize that firms can engage in ostentatious behaviors that display the firm’s affluence and robust resource base. We term these behaviors “flaunting,” and we present a two-part model that investigates how flaunting can reduce the impact of an unpredictable negative event on firm outcomes and why it is effective at doing so. In part one, we theorize how flaunting can generate net positive stakeholder group evaluations by enhancing distinctiveness among stakeholder groups. In part two, we theorize that the net positive stakeholder group evaluations can buffer the impact of an unpredictable negative event on firm outcomes. We also argue that this buffering effect is amplified when the flaunting firm actively manages stakeholder group distinctiveness. Thus, while flaunting can be both off-putting and enticing to different stakeholder groups, we theorize that courting the love of some may be worth the cost of being disliked (or worse) by others.